2017
DOI: 10.1111/jvim.14641
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment of Left Ventricular Function in Healthy Horses and in Horses with Heart Disease Using Pulsed‐Wave Tissue Doppler Imaging

Abstract: BackgroundAssessment of left ventricular (LV) function by tissue Doppler imaging (TDI) is not well established in horses with heart disease.ObjectivesTo describe the use of pulsed‐wave (PW) TDI for the assessment of LV function, establish reference intervals, investigate effects of mitral regurgitation (MR), aortic regurgitation (AR), and primary myocardial disease (MD), and provide proof of concept for the use of PW TDI in Warmblood horses with heart disease.AnimalsThirty healthy horses, 38 horses with MR, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 59 publications
2
30
2
Order By: Relevance
“…Conversely, LVST, lasting from the start of isovolumic contraction (S1) to the end of ejection (which is timely related to the second heart sound, S2) should be longer than LVET, which lasts from begin to end of ventricular ejection (aortic valve opening to closure) . This is concurrent with recent studies using tissue Doppler imaging for assessment of left ventricular function in horses, in which reported PEP (127 ± 25.3 ms; 121 ± 14.1 ms) was longer than EMAT and LVET (404 ± 18.9 ms; 421 ± 24.7 ms) was shorter than LVST reported in this study, respectively . Both EMAT and LVST are shorter in people compared to horses , which can be explained by different body mass and cardiac size.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Conversely, LVST, lasting from the start of isovolumic contraction (S1) to the end of ejection (which is timely related to the second heart sound, S2) should be longer than LVET, which lasts from begin to end of ventricular ejection (aortic valve opening to closure) . This is concurrent with recent studies using tissue Doppler imaging for assessment of left ventricular function in horses, in which reported PEP (127 ± 25.3 ms; 121 ± 14.1 ms) was longer than EMAT and LVET (404 ± 18.9 ms; 421 ± 24.7 ms) was shorter than LVST reported in this study, respectively . Both EMAT and LVST are shorter in people compared to horses , which can be explained by different body mass and cardiac size.…”
Section: Discussionsupporting
confidence: 66%
“…In a recent study, it was shown that systolic time intervals can be altered in horses with mitral and aortic insufficiency, but their clinical value could not be well documented and remains uncertain at this time . Similarly, S3 can be heard in healthy horses and in horses with heart disease, but lacking accurate methods for quantification of the strength of S3, its diagnostic and prognostic value in horses with heart disease is not well established .…”
Section: Introductionmentioning
confidence: 99%
“…Koenig et al . investigated the use of pulsed wave TDI to measure LV function in healthy horses and horses with different cardiac diseases . In that study, results from horses with AR were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of increased MWT d and RWT d in horses with mild AR indicates that some concentric remodeling occurs in this population of horses, whereas the decreased RWT d seen in the horses with severe AR indicates that the chamber enlargement is becoming disproportionate to wall thickness. The fact that indices of LV systolic function are not different among the AR severity subgroups highlights the difficulty in using these variables to judge the severity of AR, as has been described in 2 recent studies evaluating other methodologies to identify subtle changes in myocardial function …”
Section: Discussionmentioning
confidence: 94%
“…Because indices of LV size were included in the AR severity scoring system used to classify AR severity, it is logical that these indices would be different among the AR severity subgroups. The extent of LV enlargement in the AR severity subgroups was similar to that recently reported in other studies assessing the severity of AR using echocardiographic measurements . However, it is also clear that horses with severe AR show signs of LA enlargement indicating the hemodynamic relevance of severe AR resulting in increased preload of both the LV and LA.…”
Section: Discussionmentioning
confidence: 99%